L'aménagement flexible de la classe : le point de vue d'enseignantes du primaire au Québec - Mylène Leroux; Léna Bergeron; Sylvain Turcotte; Geneviève Deschênes; Jonathan Smith; Catherine Malboeuf-Hurtubise; Jessica Riel; Julie Bergeron; Félix Berrigan
Despite a growing interest for flexible classrooms in this past decade, few studies have been initiated to investigate this strategy. This exploratory study focusses on teachers' motivations and inspirations, intentions and ways of implementing flexible classroom, challenges encountered, perceived benefits, and available resources and support helping to promote this type of layout. To do so, an online survey was conducted with 27 elementary school teachers to get their perception about the aforementioned topics ; 6 of them also participated in an individual semi-structured interview. Results show that flexible classrooms may result in enhancing differentiated instruction, as it has the potential to answer pupils' needs, as well as meeting some needs of teachers themselves.